Analisis Kelayakan Finansial Usahatani Stroberi (Fragaria × ananassa) - Nur'Aisyah, Nur'Aisyah; Arifin, Samsul; pardani, cecep (Ma'soem University, 2025)
Strawberry (Fragaria × ananassa) is a horticultural commodity widely developed in the form of agritourism, one example being Haifresh Strawberry Lembang, located in Cikahuripan Village, Lembang District, West Bandung Regency. This study aims to analyze the financial feasibility of strawberry farming. The research is a case study with a descriptive quantitative approach. Data were obtained through observation, structured interviews, and documentation. The analysis was carried out using five financial feasibility indicators, namely Net Present Value, Net Benefit Cost Ratio, Gross Benefit Cost Ratio, Internal Rate of Return, and Payback Period. The results show that strawberry farming at the research site is financially feasible. The NPV reached IDR 254,339,787.00 (> 0), Net B/C was 2.34 (> 0), Gross B/C was 1.42 (> 0), IRR was 65.56% (> 6%), and the Payback Period was 1 year 1 month 7 days of the business life span. This financial feasibility analysis indicates that strawberry farming activities at Haifresh Strawberry Lembang are economically profitable and have sustainable potential as a model of environmentally friendly agriculture.